DIAGNOSTICS OF THE DIGITAL BEHAVIOR OF THE AUDIENCE OF WEBSITES OF THE HEI OF EUROPE USING THE THEORY OF GENERATION MARKETING - LISUN, Yanina (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article summarizes the values, content, and expediency of using digital marketing communications, depending on the generation of visitors to the HEI website. The age profile of the population of Ukraine and European countries in 2022–2023 was studied as a sign of the segmentation of the market of educational services according to the concept of generations. It was established that the average age of the population in 2023 in Ukraine is 43,9 years; in Poland – 42,5 years; in Germany it is slightly more – 44,9 years. In Ukraine, during 2022-2023, there is a decrease in generation Z – the age group of the population 18-24 years and a decrease in generation Z, Y (age group 25–34 years), which is caused mainly by the war against Ukraine. It is the specified age categories that make up the strategically important target audience of higher education institutions.At the same time, the experience of the European education system shows that the leading HEIs in Europe, among other things, work in a targeted manner with an audience of 0-4 years; 5-12 years; 13-17 years, providing opportunities to start in international schools and colleges belonging to one or another higher education institution. That is, higher education institutions in Europe purposefully educate their target audience, providing a full cycle of educational services, starting from the age of 0-4 years.The article analyzes the target audience of the websites of the leading higher education institutions of Ukraine, Poland, and Germany using Similsrweb digital marketing tools. Using the concept of generational marketing, the segments of visitors to HEI websites were selected: generations «Z», «Y», «X», «Baby Boomers», «Traditional». It has been established that the largest share among visitors to the websites of HEI are generation «Z» and generation «Y» Ukraine – 18%; Poland – 20%; Germany – 15% each generation respectively. The female share of website visitors predominates in classic higher education institutions, while technical higher education institutions have more male audiences. The average duration of a visit to a website among Generation Z (visitors aged 18–24) is 7–8 minutes. Women spend more time on the site. On average, about 30-35% of visitors leave a website after viewing only one page. The older the visitors to the HEI website are, the sharper the rate of attendance declines. In Ukraine, the decline in visitors of the older age group is slower than in Poland and Germany. Middle-aged and older people in Ukraine are more interested in the content posted on the websites of higher education institutions. Visitors to the websites of higher education institutions over 65 years of age, especially the female audience, spend a significant amount of time on the website of universities of Ukraine, Poland and Germany – an average of 9–10 minutes, which is even more than for the age categories 18–24 and 25–34 years. With the help of Similsrweb digital marketing toolkit, the subject of the content of the websites of the relevant higher education institutions of Ukraine, Poland, and Germany, which is most viewed by visitors, was analyzed.The most popular content topics on the websites of higher education institutions of Ukraine, Poland, and Germany are: programming, computer technologies, education, social sciences (mainly audience of Ukraine and Poland), news and media, video games (mainly audience of Poland).
Keywords: HEIs website; digital behavior of the target audience; marketing of generations; generations A; Z; Y; X; digital marketing; content strategy of HEI